Multi-type, multi-sensor placement optimization for structural health monitoring of long span bridges - Soman, Rohan N.; Onoufriou, Toula; Kyriakides, Marios; Votsis, Renos; Chrysostomou, Christis (My University, 2014)
The paper presents a multi-objective optimization strategy for a multi-type sensor placement for Structural Health Monitoring (SHM) of long span bridges. The problem is formulated for simultaneous placement of strain sensors and accelerometers (heterogeneous network) based on application demands for SHM system. Modal Identification (MI) and Accurate Mode Shape Expansion (AMSE) were chosen as the application demands for SHM. The optimization problem is solved through the use of integer Genetic Algorithm (GA) to maximize a common metric to ensure adequate MI and AMSE. The performance of the joint optimization problem solved by GA is compared with other established methods for homogenous sensor placement. The results indicate that the use of a multi-type sensor system can improve the quality of SHM. It has also been demonstrated that use of GA improves the overall quality of the sensor placement compared to other methods for optimization of sensor placement
Keywords: Long span bridge; Sensor placement optimization; Mode shape expansion; Modal identification; Modal clarity index; Genetic algorithm